El hospital de San Lázaro de la ciudad de León durante la Edad Media - Prada Villalobos, Montserrat (Estudios humanísticos. Geografía, historia y arte, 2001)
The objetive of this article is to display the development, during the Middle Ages, of one hospital placed in one of the settlements in the pilgrims'road to Santiago de Compostela: Saint Lazard's leper hospital, where people who had a contagious disease took refugee.